Mechanisms and biological significance of pulsatile hormone secretion - Chadwick, Derek; Goode, Jamie (Wiley, 2000)
Rhythmic transcription : the molecular basis of oscillatory melatonin synthesis / Nicholas S. Foulkes, Nicolas Cermakian, David Whitmore and Paolo Sassone-Corsi -- The frequency encoding of pulsatility / Albert Goldbeter, Geneviéve Dupont and José Halloy -- Timing-dependent modulation of insulin mitogenic versus metabolic signalling / Pierre De Meyts and Ronald M. Shymko -- Growth hormone pulse-activated STAT5 signalling : a unique regulatory mechanism governing sexual dimorphism of liver gene expression / David J. Waxman -- Orderliness of hormone release / Steven M. Pincus -- Prediction and significance of the temporal pattern of hormone secretion in disease states / G. Brabant and K. Prank -- Therapeutic implications of circadian rhythms in cancer patients / Francis Lévi -- Pathophysiology of human circadian rhythms / Georges Copinschi, Karine Spiegel, Rachel Leproult and Eve Van Cauter -- Nature of altered pulsatile hormone release and neuroendocrine network signalling in human ageing : clinical studies of the somatotropic, gonadotropic, corticotropic and insulin axes / Johannes D. Veldhuis -- Pulsatile insulin secretion / Peter Butler -- Control of growth hormone (GH) release by GH secretagogues / Iain C.A.F. Robinson -- Pulsatile parathyroid hormone secretion in health and disease / Franz Schaefer -- Significance of pulsatility in the HPA axis / S.L. Lightman, R.J. Windle, M.D. Julian, M.S. Harbuz, N. Shanks, S.A. Wood, Y.M. Kershaw and C.D. Ingram.
Includes bibliographical references and indexes
Use copy Restrictions unspecified star MiAaHDL
Keywords: Congress